Scientific Basis of the Audit Theory - BARANOV, Pavel P.; SHAPOSHNIKOV, Alexander A.; MAKSIMOVA, Galina V.; FADEYKINA, Natalia V. (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The article formulates, develops and researches the hypothesis that the current state of scientific theory of the audit is a serious factor provoking doubts about the ability of the audit practice to perform institutional functions of fencing the society and the economy from the information risk in decision-taking. Reveals the author's view of key reasons for criticism and rejection of audit as a systematically organized scientific knowledge. It characterizes and analyzes the international experience of theoretical development of the science about the audit positioned by authors in the context of the disciplinary matrix, the author presented structural, logical and verbal description of embodiments of the audit theory. Based on results of the study, it is argued that existing of theoretical constructs in the audit is featured by scientific theory, and the need to implement collector programs for change of scientific paradigm of the audit.